PENGARUH PENDAPATAN DAN PENGETAHUAN MASYARAKAT TENTANG ZAKAT TERHADAP KESADARAN MEMBAYAR ZAKAT MAL DI KELURAHAN TERUSAN - Mafrudho Mafrudho; Mahdayeni Mahdayeni; Alfazri Rahmadani; Dini Haryati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of income and community knowledge about zakat on awareness of paying zakat mal in Terusan Village. Zakat is one of the obligations for Muslims who have significant social and economic empowerment. However, community awareness in paying zakat still varies, influenced by various factors, including income levels and understanding of zakat. The results of the study showed that income has a positive and significant effect on awareness of paying zakat mal, namely tcount> ttable or 2.051> 1.862, which means that the higher a person's income, the greater their awareness of paying zakat. In addition, public knowledge about zakat also has a positive and significant influence on the awareness of paying zakat mal, namely tcount> ttable 4.211> 1.682. This shows that the better a person's understanding of zakat, the higher their awareness to fulfill it.